Model Pariwisata Digital dalam Pengembangan Pariwisata Indonesia - Muhammad Hilmy Aziz (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Tourism is the leading sector that positively impacts developments in all lines, both in socio-culture, especially economic growth. However, there is a gap between the tourism sector in the pre-pandemic period and during the pandemic. This is due to a significant decrease in the number of tourists. Therefore, there is a need for innovation that is no longer at the traditional level in developing Indonesian tourism but takes the digitalization path to enter the internet base. This study aims to create a new model for the development of digital tourism in the national scope. Meanwhile, the adopted library uses the AIDDA Model, developed by Kotler and Keller (2009) by adding internet elements to the model universe. The method used is descriptive qualitative, while the data analysis technique in this study is taken from the way disclosed by Miles Huberman et al. (1994). This research results that the application of digital tourism development is not only a mere issue but must be realized concretely along with the fulfillment of facilities and infrastructure related to the internet as the primary medium. The AIDDA model that was developed was then adopted as a prototype in conducting tourism marketing. The tourism digitization targets in this model are Awareness, Interest, Desire, Decision, Action to encourage tourists to explore more of the new destinations offered. As a result, tourists are not only enabled to enjoy natural attractions but also presented with a lot of educational information that is not widely disclosed when traveling independently, based on the internet.